Angioimmunoblastic T-Cell Lymphoma: A Diagnostic Challenge - Jorge Ocampo-Garza; Maira Elizabeth Herz-Ruelas; Elias Eugenio González-Lopez; Eric Eduardo Mendoza-Oviedo; Juana Irma Garza-Chapa; Sonia Sofía Ocampo-Garza; Norma Elizabeth Vázquez-Herrera; Ivett Miranda-Maldonado; Jorge Ocampo-Candiani (Karger Publishers, 2014)
Angioimmunoblastic T-cell lymphoma (AITL) accounts for 15-20% of all peripheral T-cell lymphomas. It is a rare subtype of CD4 T-cell peripheral lymphoma that affects aged individuals, causing B symptoms, generalized lymphadenopathy and hepatosplenomegaly. Its pathogenesis is still unclear, but in some cases it has been associated with infection, allergic reaction or drug exposure. The majority of patients are diagnosed in an advanced stage and anthracycline based regimen is considered the first-line therapy. Skin involvement is not well characterized, occurring in up to 50% of patients and presenting as nonspecific rash, macules, papules, petechiae, purpura, nodules and urticaria. We present the illustrative case of a 55-year-old woman with an AITL who presented prominent skin findings, arthritis, lymphadenopathy and hypereosinophilia. Skin biopsy reported a T-cell lymphoma and the diagnosis of AITL was confirmed by an axillary lymph node biopsy, which was also positive for Epstein-Barr virus. Chemotherapy with CHOP-21 and thalidomide was given, accomplishing complete remission after six cycles.